Problematizing Social Justice in Health Pedagogy and Youth Sport: Intersectionality of Race, Ethnicity, and Class. Issue 3 (2nd July 2016) - Dagkas, Symeon
Abstract : Social justice education recognizes the discrepancies in opportunities among disadvantaged groups in society. The purpose of the articles in this special topic on social justice is to (a) provide a critical reflection on issues of social justice within health pedagogy and youth sport of Black and ethnic-minority (BME) young people; (b) provide a framework for the importance of intersectionality research (mainly the intersection of social class, race, and ethnicity) in youth sport and health pedagogy for social justice; and (c) contextualize the complex intersection and interplay of social issues (i.e., race, ethnicity, social classes) and their influence in shaping physical culture among young people with a BME background. The article argues that there are several social identities in any given pedagogical terrain that need to be heard and legitimized to avoid neglect and "othering." This article suggests that a resurgence of interest in theoretical frameworks such as intersectionality can provide an effective platform to legitimize "non-normative bodies" (diverse bodies) in health pedagogy and physical education and sport by voicing positionalities on agency and practice.